Translational Model‐Informed Dose Selection for a Human Positron Emission Tomography Imaging Study of JNJ‐54175446, a P2X7 Receptor Antagonist - Yan Xu; Xin Miao; Paulien Ravenstijn; Anja Hijzen; Mark E. Schmidt; Partha Nandy; Honghui Zhou (Wiley, 2020)
Positron emission tomography (PET) provides useful information in target engagement or receptor occupancy in the brain for central nervous system (CNS) drug development, however, dose selection for human PET studies is challenging and largely empirical. Here, we describe a translational pharmacokinetic/pharmacodynamic (PK/PD) modeling work to inform dose selection for a human PET study of JNJ‐54175446, a CNS‐penetrating P2X7 receptor antagonist. Models were developed using data on monkey brain occupancy and plasma drug exposures from a monkey PET study and early human clinical studies that provided data on drug exposures and human ex vivo‐stimulated peripheral interleukin (IL)‐1β release. The observed plasma PK of JNJ‐54175446 in human was adequately described by a one‐compartment model with parallel zero‐order and first‐order absorption and first‐order elimination. An exposure‐occupancy model was extrapolated from monkey to human assuming a similar unbound potency (all other model parameters remained unchanged). This model was then used to simulate human brain occupancy to guide human PET study dose selection, together with the human population PK model. The corroboration of model predicted occupancy by the observed occupancy data from the human PET study supports the use of a monkey as a predictive model for human PET target engagement. Potency estimate for brain occupancy was generally comparable to that for the suppression of the provoked peripheral IL‐1β release ex vivo, indicating that blood IL‐1β release may be used as a surrogate of central occupancy for JNJ‐54175446. Translational PK/PD modeling approach could be used for selecting optimal doses for human PET and other clinical studies.